1989
DOI: 10.1103/physrevc.39.311
|View full text |Cite
|
Sign up to set email alerts
|

Isovector and isoscalar spin-flip excitations in even-evens-dshell nuclei excited by inelastic proton scattering

Abstract: Forward-angle cross sections for 1+ states have been measured in ' Mg, Si, and S by 201 MeV proton inelastic scattering. Comparisons are made with (y, y'), (e, e'), and (p, n) results. The measured strength is compared with microscopic distorted-wave Born approximation calculations using large-scale shell-model wave functions. Ratios of experimental to theoretical 1 strengths are given. Almost no quenching is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 23 publications
3
38
0
Order By: Relevance
“…As already noted in section III A, a number of excited states near the α-particle and neutron thresholds in 26 Mg have been observed by additional inelastic proton scattering experiments [49,50,52]. However, their spins and parities have not been determined.…”
Section: Reaction Rates Formentioning
confidence: 82%
See 1 more Smart Citation
“…As already noted in section III A, a number of excited states near the α-particle and neutron thresholds in 26 Mg have been observed by additional inelastic proton scattering experiments [49,50,52]. However, their spins and parities have not been determined.…”
Section: Reaction Rates Formentioning
confidence: 82%
“…The lowest energy resonance measured in those works is located at E lab r ≈ 830 keV, near the high energy end of the astrophysically important region. The structure of the 26 Mg compound nucleus near the α-particle and neutron thresholds has been investigated previously via neutron capture [46,47], scattering [48][49][50], photoexcitation [51][52][53], transfer [44,[54][55][56], and photoneutron measurements [57]. In particular, the latter study observed the strong population of a 26 Mg level near E x = 11150 keV, with presumed quantum numbers of J π = 1 − , corresponding to an expected low-energy resonance at E cm = 450 keV.…”
Section: A General Aspectsmentioning
confidence: 99%
“…A number of scattering and transfer measurements ( [50], [51], [52], [42], [53], [54] and [55]) have been performed to investigate the level structure of 26 Mg above the α-threshold. 26 Mg by Longland et al [55] and deBoer et al [58] and 26 Mg(γ, n) 25 Mg measurement by deBoer et al [59].…”
Section: Level Density and Alpha Cluster Structurementioning
confidence: 99%
“…These measurements have been unable to access the astrophysical energy region because of the relatively high α penetrability through the Coulomb barrier as well as unwanted background from cosmic rays and beam induced reactions. Therefore several indirect experiments have been conducted to study the compound nucleus of interest 26 Mg [16][17][18][19][20][21][22][23][24][25]. Most of these experiments have only yielded energy information for states, leaving partial decay widths and spin-parities largely unknown.…”
Section: Introductionmentioning
confidence: 99%